Students' English Language performance in a multicultural classroom setting / Raimei Christina a/p Michael - Michael, Raimei Christina (2012)
English language was introduced as the compulsory second language in the secondary schools of Malaysia (Asmah Hj. Omar, 1979, as quoted in Solomon, 1988). The central focus of the Secondary School English Language Programme in KBSM is the development of the four language skills: reading, writing, listening and speaking (Hassan and Selamat, 2002). This study aims to investigate Form 4 school students’ English language performance in a multicultural classroom setting. Firstly, this study attempts to evaluate students’ comprehending performance in reading and listening skills using the Malaysian Education grading system (2010) and Krashen’s comprehensible input (1985 as quoted in Wu, 2010). Secondly, this study tries to classify the errors in writing and speaking skills by applying the Keshavarz’ model (1999 as cited in Zarei, 2011) and lastly, analyse the appropriateness of student’ speech events to the topic of discussion using S-P-E-A-K-I-N-G model proposed by Hymes (1974 as cited in Lee, 2007). 18 Form 4 students were selected randomly for this study as respondents. Data was collected by asking the respondents to complete a set of questionnaires that consists 5 sections: biographical background, reading task, writing task, listening task and speaking task. Respondents were asked to read 5 different genres of texts and then to choose and write suitable answers for the reading task. For the writing task, each respondent was asked to write an essay incorporating different aspects of culture with reference to the Malaysian multicultural situation. Respondents listened to an audio CD in order to complete the listening task. Out of the 18 respondents, only 10 respondents participated in the speaking task, the remaining 8 respondents were sitting for the year end examination at the time of recording. The results obtained show that, the comprehending performance of all of the Indian students is higher when compared to the Chinese and Malay respondents. The frequent occurrence of errors in the writing and speaking are found in the morphological and syntactical levels of the structure. All respondents’ speech was analysed using the SP- E-A-K-I-N-G model (Hymes, 1974 as cited in Lee, 2007) to discover the appropriateness to the topic of discussion. It was found that the speeches of all the respondents from all three ethnic groups are found to be appropriate to the topic of discussion.